Perfil de Conocimiento Financiero y Edad en los Estudiantes de Bachillerato de Instituciones del Sistema Público - Colala Alverca, Brygitte Stefania (2023)
Financial education is an area that in recent years has gained importance in secondary education, as it is important for financial decision-making, this enables people to improve their understanding of financial concepts and products, prevent fraud, and make correct decisions. to their needs, therefore, it is essential that financial education begin to be taught from an early age, for this, the objective of the present investigation is to evaluate the relationship between the level of financial education and the age variable in the educational institutions of the system public Developing a non-experimental investigation with cross section, mixed approach; quantitative, for the elaboration of statistical data collected from the research project, called: Panorama of the use of ICTs for the strengthening of financial education in "the centennials" of the public and private educational institutions of the city of Loja and thus be able to determine the relationship between financial knowledge and the age variable of the students, and qualitatively for the preparation of the proposal and design of the financial education guide. The main results reflect that the students have a level 3 of financial knowledge, in addition, it was evidenced that there is a low positive confirmation, which indicates that age is not significantly related to the financial knowledge that students have. Finally, it can be concluded that students can apply their knowledge of financial concepts and commonly used products to relevant situations for them, however, it is important that they continue training in this subject for proper informed decision making.